3MAX catheter for thromboaspiration of downstream and new territory emboli after mechanical thrombectomy of large vessel occlusions: initial experience. Issue 3 (June 2019) - Settecase, Fabio
Distal emboli and emboli to new territories occur in up to 14% and 11% of large vessel occlusion mechanical thrombectomies, respectively. A retrospective review was conducted of 18 consecutive patients with large vessel occlusion acute stroke undergoing mechanical thrombecomy, subsequently developing distal emboli and/or emboli to new territory for which thromboaspiration using the 3MAX catheter was performed. Eighteen distal emboli and two emboli to new territory in 18 patients were treated in the distal M2 and M3 middle cerebral artery, pericallosal and callosomarginal arteries, and P2 posterior cerebral artery (all arteries ≥1.5 mm in diameter). 3MAX thromboaspiration was successful in 13/18 distal emboli and 2/2 emboli to new territory (total 15/20, 75%). 3MAX thromboaspiration resulted in improvement in the final modified treatment in cerebral ischaemia (mTICI) score in 14/18 patients (78%) compared with the initial mTICI score after large vessel occlusion thrombectomy. A shift towards higher final mTICI scores was seen with 3MAX catheter aspiration of distal emboli in this series. The initial mTICI score after large vessel occlusion thrombectomy was 2A in 4/18 (22%) patients and 2B in 14/18 (78%) patients. The final mTICI score after distal emboli/emboli to new territory aspiration improved to 2B in 7/18 (39%) patients, 2C in 3/18 (17%) patients and 3 in 8/18 (44%) patients. No procedural complications were noted. In 13 patients with successful distal emboli/emboli to new territory thromboaspiration, a 90-day modified Rankin score of 0–2 was seen in 10 patients (77%). In five patients with unsuccessful distal emboli/emboli to new territory aspiration, a 90-day modified Rankin score of 0–2 was seen in three patients (60%). 3MAX thromboaspiration of select distal emboli and emboli to new territories is feasible. Larger prospective studies are needed to establish the clinical benefit and safety of this approach.